Kinetic model of microwave-induced quaternarization using dimensional analysis. (23rd November 2022) - Zou, Minting; Mao, Taoyan; Li, Min; Mu, Yuxin; Pan, Lei; Zheng, Cheng
Highlights: Kinetics of reaction of tetradecyl methyl dihydroxyethyl ammonium bromide at boiling temperature. The important factors affecting the microwave reaction rate were selected and the microwave reaction kinetics model was established by dimensional analysis. The generality of the model was verified by the same series of quaternary amine reactions. Abstract: Microwave heating typically hastens the reaction rate and reduces the reaction time of a chemical reaction; thus, it has been gaining attention in organic synthesis research. However, a microwave reaction kinetics model is required during the scale up of a process design in an industrial application. Here, a microwave reaction kinetics model was derived by using dimensional analysis with model parameters, which were determined by nonlinear fitting of experimental data using Matlab. A comparison between the model estimated and experimental values indicated that the error quantitative correlation was small, indicating the validity of the kinetics model.